Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - Hao, You-You; Zhu, Zhuo-Yi; Fang, Fu-Tao; Novak, Tihana; Čanković, Milan; Hrustić, Enis; Ljubešić, Zrinka; Li, Ming; Du, Jin-Zhou; Zhang, Rui-Feng; Gašparović, Blaženka (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which finally determines the riverine flux effect to coasts. Nutrients, organic carbon as well as pigments and amino acids (AAs) were collected during field observations to the eutrophic Wenchang River Estuary (WRE) and the oligotrophic Krka River Estuary (KRE) in this study for a better understanding of estuaries modification of terrestrial materials. We found a clear addition followed by removal of dissolved inorganic nitrogen (DIN) (over 100 μM) in the WRE, whereas DIN in the KRE showed very little variation along with salinity increase, ranging between 1.0 to 5.8 μM. The elevated algal derived organic carbon and increase in dissolved organic nitrogen and particulate AAs nitrogen suggests that the OM assimilation may explain up to one third of the DIN removal in the WRE, with the rest potentially be lost due to inorganic nitrogen cycling process. Due to the strong estuarine nitrogen removal/assimilation process, DIN/DIP ratio was 425 in the riverine parts, but it dropped to as low as 7 in the lower WRE, even lower when compared to the DIN/DIP ratio for the lower KRE (min. = 4). When compared with other rivers worldwide, the Wenchang River showed very high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g. DIN removal) between the KRE and WRE, apparent high nutrient yield from eutrophic rivers should be viewed with care in ocean studies as the final impact to coastal zone could be similar with the oligotrophic rivers.